Systematic Literature Review: Pengaruh Audit Laporan Keuangan dan Peran Internal Audit terhadap Kualitas Laporan Keuangan - Fianda Prathitaningtyas; Manda Azalia Nur Raissa; Dien Noviany Rahmatika (Jurnal Ilmiah Ekonomi, Akuntansi, dan Pajak, 2024)
The purpose of this study is to understand the impact of the role of internal audit and financial statement audits on the quality of financial statements. Internal audit has the task of internal supervision, needed by the company in order to understand the quality of financial statements so that the company can monitor the development of the company. In managing the company, the most effective and efficient mechanism for managers is disclosure in financial reporting. This research method is conducted with SLR (Systematic Literature Review) which is used to evaluate and review all research. Data searches were conducted using the Publish or Perish application which accessed the Google Scholar, Semantic and Crossref databases and resulted in 47 journals to be reviewed. The result is that internal audit and financial statement audit have a positive impact on the quality of financial statements.